A mortar material capable of releasing negative ions and its preparation method and application

By using rare earth oxide modified bamboo charcoal powder and zinc oxide modified tourmaline powder in mortar materials, the problem of limited negative ion release in the existing technology is solved, and efficient and stable negative ion release is achieved, satisfying the modern Building needs for health and environmental protection.

CN118637874BActive Publication Date: 2024-12-20BEIJING ECO HOME (LETING) TECH DEV CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411110457.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-20
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The existing mortar materials that can release negative ions are limited in release and it is difficult to maintain negative ions for a long time, which cannot meet the high requirements of modern buildings for health and environmental protection.

Method used

Rare earth oxide modified bamboo charcoal powder and zinc oxide modified tourmaline powder are used as negative ion components, combined with materials such as cement and epoxy resin, and through modification treatment and photocatalytic action, a mortar material that stabilizes negative ions for a long time is achieved.

Benefits of technology

It significantly increases the negative ion release and duration of the mortar material, can effectively clean the air, improve human health, and provide healthy and environmentally friendly building materials solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, and specifically discloses a mortar material capable of releasing negative ions, and a preparation method and application thereof. The mortar material capable of releasing negative ions includes the following raw material components by mass: 70-90 parts of cement, 40-60 parts of lime powder, 100-120 parts of standard sand, 1-2 parts of water reducer, 3-5 parts of dispersant, 60-100 parts of negative ion components, 0.05-0.1 parts of stabilizer, 30-50 parts of epoxy resin and 70-100 parts of water. Wherein, the negative ion component includes rare earth oxide modified bamboo charcoal powder and zinc oxide modified tourmaline powder. The mortar material provided by the present invention can stably and long-term release a large amount of negative ions, so as to achieve the purpose of cleaning air and benefiting human health. The present invention effectively solves the problem that the mortar material capable of releasing negative ions in the prior art has a certain negative ion release capacity, but the release amount is limited and it is difficult to maintain the release of negative ions for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and specifically discloses a mortar material capable of releasing negative ions, a preparation method and application thereof. Background Art

[0002] Negative air ions not only have the effects of antibacterial and odor-inhibiting, freshness preservation, purification and dust removal, but also can prevent human respiratory diseases, improve sleep, anti-oxidation, anti-aging, remove free radicals in the body, reduce blood viscosity, etc., which are very beneficial to human health. Studies have shown that the health care effect and therapeutic effect of negative air ions on the human body are related to the concentration of negative air ions. Only when the concentration of negative ions is greater than that of positive ions, people will feel comfortable, and it has a therapeutic effect on many diseases. Based on this, how to use building materials to increase the concentration of negative ions in the air has become a hot research issue in the field of ecological building materials.

[0003] In the prior art, most of the methods are to add negative ion materials to building materials to increase the amount of negative ions released. For example, the prior art reports that adding tourmaline to mortar can make the resulting mortar material have the ability to release negative ions, and the release amount can reach 1000 / cm 3 , which can effectively inhibit various skin diseases caused by cement. However, with the development of society, people have higher and higher requirements for the environment, and the harmful bacteria and formaldehyde content in the air are getting higher and higher. There is an urgent need for a building mortar material that can release a large amount of air negative ions. Although the existing mortar materials have a certain ability to release negative ions, the release amount is limited, and it is difficult to maintain the release of negative ions for a long time. Based on this, the development of a mortar material that can release a large amount of negative ions for a long time is of great practical significance for emerging building materials. Summary of the invention

[0004] In view of the problem that the mortar material capable of releasing negative ions in the prior art has a certain negative ion release capacity, but the release amount is limited and it is difficult to maintain the negative ion release for a long time, the present invention provides a mortar material capable of releasing negative ions, and a preparation method and application thereof. The mortar material capable of releasing negative ions is prepared with cement and epoxy resin as gelling materials; lime powder, standard sand, and negative ion components as aggregates; and water reducer, dispersant, and stabilizer as additives. The negative ion component can release a large amount of negative ions for a long time, and combined with other raw material components, the obtained mortar material can achieve the purpose of cleaning the air and benefiting human health.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The first aspect of the present invention provides a mortar material capable of releasing negative ions, comprising the following raw material components in parts by weight: 70-90 parts of cement, 40-60 parts of lime powder, 100-120 parts of standard sand, 1-2 parts of water reducer, 3-5 parts of dispersant, 60-100 parts of negative ion component, 1-2 parts of stabilizer, 30-50 parts of epoxy resin and 70-100 parts of water;

[0007] The negative ion component comprises a first component and a second component; the first component is bamboo charcoal powder modified by rare earth oxide; and the second component is tourmaline powder modified by zinc oxide.

[0008] Bamboo charcoal powder is a material with a honeycomb porous structure obtained by high-temperature calcination, and has excellent adsorption, antibacterial and negative ion emission properties. However, bamboo charcoal powder is prone to agglomeration, resulting in a greatly weakened negative ion release capacity. Based on this, the present invention modifies the bamboo charcoal powder, and rare earth elements are added to the bamboo charcoal structure. Since the β decay of isotopes in the rare earth elements will produce an appropriate amount of electrons, the electrostatic repulsion of the electrons is used to avoid the bamboo charcoal powder from agglomerating, which is conducive to the release of negative ions from the bamboo charcoal powder. In addition, the present invention also designs a zinc oxide modified tourmaline powder. Based on the characteristic that zinc oxide has photocatalytic properties, electrons and holes can be generated by the photovoltaic effect, and negative oxygen ions can be generated by the action of photogenerated electrons and oxygen. However, the recombination rate of photogenerated electrons and holes in zinc oxide is high and very rapid. Therefore, the present invention introduces tourmaline powder, and the tourmaline powder is used to reduce the probability of photogenerated electron-hole recombination of zinc oxide, which also leads to a large amount of electrons and energy on the surface of the zinc oxide modified tourmaline powder, which is easier to dissociate air molecules to generate a large amount of negative ions. Moreover, since tourmaline powder itself has a permanent polarization effect, it can continuously release negative ions, and combined with zinc oxide materials, it can achieve the purpose of long-term and stable release of negative ions. Furthermore, since rare earth elements can also promote the further dissociation of tourmaline powder into air, the concentration of negative ions generated can be further increased.

[0009] The invention adds the negative ion component to the mortar material to effectively improve the ability of the mortar material to release negative ions, obtain a mortar material that can stably and long-term release negative ions, and achieve the purpose of cleaning the air and improving human health. The technical solution of the invention can effectively solve the problem that the mortar material that can release negative ions in the prior art has a limited release amount and is difficult to maintain negative ion release for a long time, and provide a new idea and theoretical basis for healthy and environmentally friendly building materials.

[0010] Preferably, the mass ratio of the first component to the second component is 1:1.5-1:2.

[0011] Preferably, the rare earth oxide in the rare earth oxide-modified bamboo charcoal powder is any one or more of cerium oxide, europium oxide or lanthanum oxide.

[0012] Preferably, the method for preparing the rare earth oxide modified bamboo charcoal powder comprises the following steps:

[0013] S1, ball-milling the bamboo charcoal, heating it to 200°C-300°C for pretreatment, and obtaining pretreated bamboo charcoal powder;

[0014] S2. The pretreated bamboo charcoal and rare earth oxide are uniformly mixed, firstly subjected to a heat treatment at 420° C.-520° C., and then heated to 650° C.-750° C. for a secondary heat treatment to obtain rare earth oxide modified bamboo charcoal powder.

[0015] Further preferably, in S1, the temperature is increased by programmed temperature increase at a rate of 10°C / min-15°C / min.

[0016] Further preferably, in S1, the pretreatment time is 3h-6h.

[0017] Further preferably, in S1, the rotation speed of the ball mill is 800 rpm-1000 rpm, and the ball milling time is 30 min-40 min.

[0018] Further preferably, in S2, the mass ratio of the pretreated bamboo charcoal powder to the rare earth oxide is 10:1-10:1.5.

[0019] Further preferably, in S2, the holding time of the primary heat treatment is 2h-4h.

[0020] Further preferably, in S2, the holding time of the secondary heat treatment is 5h-8h.

[0021] Further preferably, in S2, the primary heat treatment and the secondary heat treatment are both heated by programmed temperature increase, wherein the heating rate of the primary heat treatment is 10°C / min-20°C / min, and the heating rate of the secondary heat treatment is 5°C / min-10°C / min.

[0022] Preferably, the method for preparing the zinc oxide modified tourmaline powder comprises the following steps:

[0023] Step a, dissolving zinc salt in an alcohol solution, adding a strong base, mixing evenly, separating the solid from the liquid, washing, and drying to obtain zinc oxide powder;

[0024] Step b, adding tourmaline powder to the zinc oxide powder for ball milling, heating to 200° C.-300° C. for calcination to obtain zinc oxide modified tourmaline powder.

[0025] Further preferably, in step a, the zinc salt is any one of zinc acetate, zinc chloride, zinc sulfate or zinc nitrate.

[0026] Further preferably, in step a, the strong base is potassium hydroxide or sodium hydroxide.

[0027] Further preferably, in step a, the alcohol solution is a 50%-65% ethanol solution.

[0028] Further preferably, in step a, the mass volume ratio of the zinc salt to the alcohol solution is 1g:3mL-1g:5mL.

[0029] Further preferably, in step a, the mass ratio of the zinc salt to the strong base is 1:0.05-3:0.1.

[0030] Further preferably, in step b, the mass ratio of the zinc oxide powder to the tourmaline powder is 1:8-1:10.

[0031] Further preferably, in step b, the rotation speed of the ball mill is 500 rpm-800 rpm, and the ball milling time is 20 min-40 min.

[0032] Further preferably, in step b, the calcination time is 3h-6h.

[0033] Further preferably, in step b, the temperature is increased by programmed temperature increase at a rate of 5°C / min-10°C / min.

[0034] Preferably, the cement is Portland cement.

[0035] Preferably, the particle size of the lime powder is 0.2 mm-0.4 mm.

[0036] Preferably, the particle size of the standard sand is 0.3 mm-0.5 mm.

[0037] Preferably, the water reducer is any one of a sodium lignin sulfonate water reducer, a naphthalene-based high-efficiency water reducer, an aliphatic high-efficiency water reducer, an amino high-efficiency water reducer or a polycarboxylic acid high-efficiency water reducer.

[0038] Preferably, the dispersant is a fatty acid dispersant.

[0039] Preferably, the stabilizer is any one of EL0002, TAB-2 or T-386.

[0040] The second aspect of the present invention provides a method for preparing the mortar material capable of releasing negative ions, comprising the following steps: weighing each raw material component according to the designed ratio, and mixing the weighed components uniformly to obtain the mortar material capable of releasing negative ions.

[0041] The third aspect of the present invention provides the use of the mortar material capable of releasing negative ions or the mortar material capable of releasing negative ions prepared by the preparation method of the mortar material capable of releasing negative ions in the field of building materials.

[0042] In summary, the present invention uses cement and epoxy resin as cementitious materials; lime powder, standard sand, and negative ion components as fine aggregates; and water reducer, dispersant, and stabilizer as additives to prepare a mortar material capable of releasing negative ions. The mortar material capable of releasing negative ions can release negative ions stably for a long time, and the release amount is large, which can achieve the purpose of cleaning the air and benefiting human health. The use of the mortar material can effectively solve the problem that the mortar material capable of releasing negative ions in the prior art has a certain negative ion release capacity, but the release amount is limited and it is difficult to maintain the release of negative ions for a long time. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] This embodiment provides a mortar material capable of releasing negative ions and a preparation method thereof, which specifically includes the following contents:

[0046] The mortar material capable of releasing negative ions comprises the following raw material components by weight: 80 parts of silicate cement, 50 parts of lime powder, 110 parts of standard sand, 1.5 parts of sodium lignin sulfonate water reducer, 4 parts of fatty acid dispersant, 80 parts of negative ion component, 1 part of EL0002 stabilizer, 40 parts of epoxy resin and 80 parts of water;

[0047] Wherein, the negative ion component comprises cerium oxide modified bamboo charcoal powder and zinc oxide modified tourmaline powder in a mass ratio of 1:1.6.

[0048] Weigh each raw material component according to the designed proportion, mix the weighed components evenly, and obtain a mortar material capable of releasing negative ions.

[0049] The method for preparing the cerium oxide modified bamboo charcoal powder comprises the following steps:

[0050] S1. Ball mill 100 g of bamboo charcoal at a speed of 900 rpm for 35 min, put it into a muffle furnace, heat it to 240 ° C at a heating rate of 12 ° C / min for pretreatment, and keep it warm for 4 hours to obtain pretreated bamboo charcoal powder;

[0051] S2. The pretreated bamboo charcoal was uniformly mixed with 12 g of cerium oxide, and the mixture was first heat treated at 450° C. at a rate of 15° C. / min and kept at that temperature for 3 h; then the mixture was heat treated at 690° C. at a rate of 8° C. / min and kept at that temperature for 6 h to obtain cerium oxide modified bamboo charcoal powder.

[0052] The preparation method of the zinc oxide modified tourmaline powder comprises the following steps:

[0053] Step a, dissolving 30 g of zinc acetate in 130 mL of 60% ethanol solution, adding 0.2 g of sodium hydroxide, ultrasonicating for 20 min, mixing evenly, separating the solid and the liquid, washing, and vacuum drying at 80° C. and 0.8 MPa for 2 h to obtain zinc oxide powder;

[0054] Step b: add 280 g of tourmaline powder to the zinc oxide powder, ball mill at a speed of 600 rpm for 30 min, and then heat to 250° C. at a heating rate of 10° C. / min and calcine for 5 h to obtain zinc oxide modified tourmaline powder.

[0055] The particle size of the lime powder is 0.3 mm; the particle size of the standard sand is 0.5 mm.

[0056] Example 2

[0057] This embodiment provides a mortar material capable of releasing negative ions and a preparation method thereof, which specifically includes the following contents:

[0058] The mortar material capable of releasing negative ions comprises the following raw material components by weight: 75 parts of silicate cement, 60 parts of lime powder, 120 parts of standard sand, 2 parts of sodium lignin sulfonate water reducer, 5 parts of fatty acid dispersant, 75 parts of negative ion component, 2 parts of T-386 stabilizer, 50 parts of epoxy resin and 70 parts of water;

[0059] Wherein, the negative ion component comprises lanthanum oxide modified bamboo charcoal powder and zinc oxide modified tourmaline powder in a mass ratio of 1:1.5.

[0060] Weigh each raw material component according to the designed proportion, mix the weighed components evenly, and obtain a mortar material capable of releasing negative ions.

[0061] The method for preparing the lanthanum oxide modified bamboo charcoal powder comprises the following steps:

[0062] S1. Ball mill 100 g of bamboo charcoal at a speed of 900 rpm for 35 min, put it into a muffle furnace, heat it to 220 ° C at a heating rate of 10 ° C / min for pretreatment, and keep it warm for 6 hours to obtain pretreated bamboo charcoal powder;

[0063] S2. The pretreated bamboo charcoal is uniformly mixed with 15 g of lanthanum oxide, and the mixture is first heat-treated at 420° C. at a rate of 10° C. / min and kept at that temperature for 4 h; then the mixture is heat-treated at 650° C. at a rate of 10° C. / min and kept at that temperature for 8 h to obtain lanthanum oxide-modified bamboo charcoal powder.

[0064] The preparation method of the zinc oxide modified tourmaline powder comprises the following steps:

[0065] Step a, dissolving 30 g of zinc acetate in 125 mL of 55% ethanol solution, adding 0.2 g of potassium hydroxide, ultrasonicating for 20 min, mixing evenly, separating the solid and the liquid, washing, and vacuum drying at 80° C. and 0.8 MPa for 2 h to obtain zinc oxide powder;

[0066] Step b: add 280 g of tourmaline powder to the zinc oxide powder and ball mill at a speed of 800 rpm for 30 min, then heat the mixture to 200° C. at a heating rate of 10° C. / min and calcine for 6 h to obtain zinc oxide modified tourmaline powder.

[0067] The particle size of the lime powder is 0.3 mm; the particle size of the standard sand is 0.5 mm.

[0068] Example 3

[0069] This embodiment provides a mortar material capable of releasing negative ions and a preparation method thereof, which specifically includes the following contents:

[0070] The mortar material capable of releasing negative ions comprises the following raw material components in parts by weight: 90 parts of silicate cement, 60 parts of lime powder, 100 parts of standard sand, 2 parts of sodium lignin sulfonate water reducer, 5 parts of fatty acid dispersant, 65 parts of negative ion component, 1 part of TAB-2 stabilizer, 50 parts of epoxy resin and 100 parts of water;

[0071] Wherein, the negative ion component comprises europium oxide modified bamboo charcoal powder and zinc oxide modified tourmaline powder in a mass ratio of 1:2.

[0072] Weigh each raw material component according to the designed proportion, mix the weighed components evenly, and obtain a mortar material capable of releasing negative ions.

[0073] The preparation method of the europium oxide modified bamboo charcoal powder comprises the following steps:

[0074] S1. Ball mill 100 g of bamboo charcoal at a speed of 900 rpm for 35 min, put it into a muffle furnace, heat it to 240 ° C at a heating rate of 12 ° C / min for pretreatment, and keep it warm for 4 hours to obtain pretreated bamboo charcoal powder;

[0075] S2. The pretreated bamboo charcoal is uniformly mixed with 10 g of europium oxide, and the mixture is first heat-treated at 450° C. at a rate of 15° C. / min and kept at that temperature for 3 h; then the mixture is heat-treated at 690° C. at a rate of 8° C. / min and kept at that temperature for 6 h to obtain europium oxide-modified bamboo charcoal powder.

[0076] The preparation method of the zinc oxide modified tourmaline powder comprises the following steps:

[0077] Step a, dissolving 30 g of zinc acetate in 145 mL of 65% ethanol solution, adding 0.2 g of sodium hydroxide, ultrasonicating for 20 min, mixing evenly, separating the solid and the liquid, washing, and vacuum drying at 80° C. and 0.8 MPa for 2 h to obtain zinc oxide powder;

[0078] Step b: add 280 g of tourmaline powder to the zinc oxide powder, ball mill at a speed of 600 rpm for 30 min, and then heat to 250° C. at a heating rate of 10° C. / min and calcine for 5 h to obtain zinc oxide modified tourmaline powder.

[0079] The particle size of the lime powder is 0.3 mm; the particle size of the standard sand is 0.5 mm.

[0080] Comparative Example 1

[0081] This comparative example provides a mortar material capable of releasing negative ions and a preparation method thereof, which is different from Example 1 in that the negative ion component is only cerium oxide modified bamboo charcoal powder, and other components and processes remain unchanged, specifically including the following contents:

[0082] The mortar material capable of releasing negative ions comprises the following raw material components by weight: 80 parts of silicate cement, 50 parts of lime powder, 110 parts of standard sand, 1.5 parts of sodium lignin sulfonate water reducer, 4 parts of fatty acid dispersant, 80 parts of cerium oxide modified bamboo charcoal powder, 1 part of EL0002 stabilizer, 40 parts of epoxy resin and 80 parts of water;

[0083] Weigh each raw material component according to the designed proportion, mix the weighed components evenly, and obtain a mortar material capable of releasing negative ions.

[0084] The method for preparing the cerium oxide modified bamboo charcoal powder comprises the following steps:

[0085] S1. Ball mill 100 g of bamboo charcoal at a speed of 900 rpm for 35 min, put it into a muffle furnace, heat it to 240 ° C at a heating rate of 12 ° C / min for pretreatment, and keep it warm for 4 hours to obtain pretreated bamboo charcoal powder;

[0086] S2. The pretreated bamboo charcoal was uniformly mixed with 12 g of cerium oxide, and the mixture was first heat treated at 450° C. at a rate of 15° C. / min and kept at that temperature for 3 h; then the mixture was heat treated at 690° C. at a rate of 8° C. / min and kept at that temperature for 6 h to obtain cerium oxide modified bamboo charcoal powder.

[0087] The particle size of the lime powder is 0.3 mm; the particle size of the standard sand is 0.5 mm.

[0088] Comparative Example 2

[0089] This comparative example provides a mortar material capable of releasing negative ions and a preparation method thereof, which is different from Example 1 in that the negative ion component is only zinc oxide modified tourmaline powder, and other components and processes remain unchanged, and specifically includes the following contents:

[0090] The mortar material capable of releasing negative ions comprises the following raw material components by weight: 80 parts of silicate cement, 50 parts of lime powder, 110 parts of standard sand, 1.5 parts of sodium lignin sulfonate water reducer, 4 parts of fatty acid dispersant, 80 parts of zinc oxide modified tourmaline powder, 1 part of EL0002 stabilizer, 40 parts of epoxy resin and 80 parts of water;

[0091] Weigh each raw material component according to the designed proportion, mix the weighed components evenly, and obtain a mortar material capable of releasing negative ions.

[0092] The preparation method of the zinc oxide modified tourmaline powder comprises the following steps:

[0093] Step a, dissolving 30 g of zinc acetate in 130 mL of 60% ethanol solution, adding 0.2 g of sodium hydroxide, ultrasonicating for 20 min, mixing evenly, separating the solid and the liquid, washing, and vacuum drying at 80° C. and 0.8 MPa for 2 h to obtain zinc oxide powder;

[0094] Step b: add 280 g of tourmaline powder to the zinc oxide powder, ball mill at a speed of 600 rpm for 30 min, and then heat to 250° C. at a heating rate of 10° C. / min and calcine for 5 h to obtain zinc oxide modified tourmaline powder.

[0095] The particle size of the lime powder is 0.3 mm; the particle size of the standard sand is 0.5 mm.

[0096] In order to further reflect the technical effect of the present invention, the present invention conducted the following tests on the mortar materials obtained in Examples 1-3 and Comparative Examples 1-2: the compressive strength and flexural strength were tested with reference to the standard of GB / T17671-2021, and the negative ion release concentration of the mortar samples was tested according to JC / T1016-2006 "Test Method for Negative Ion Generation of Materials"; the results are shown in Table 1.

[0097] Table 1 Performance test results of various mortar materials

[0098]

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A mortar material capable of releasing negative ions, characterized in that: The raw material components include the following parts by weight: 70-90 parts of cement, 40-60 parts of lime powder, 100-120 parts of standard sand, 1-2 parts of water reducer, 3-5 parts of dispersant, 60-100 parts of negative ion component, 1-2 parts of stabilizer, 30-50 parts of epoxy resin and 70-100 parts of water; Wherein, the negative ion component includes a first component and a second component; the first component is rare earth oxide modified bamboo charcoal powder; the second component is zinc oxide modified tourmaline powder; The mass ratio of the first component to the second component is 1:1.5-1:2; The rare earth oxide in the rare earth oxide modified bamboo charcoal powder is any one or more of cerium oxide, europium oxide or lanthanum oxide; The preparation method of the rare earth oxide modified bamboo charcoal powder comprises the following steps: S1, ball-milling the bamboo charcoal, heating it to 200°C-300°C for pretreatment, and obtaining pretreated bamboo charcoal powder; S2, mixing the pretreated bamboo charcoal powder and rare earth oxide uniformly, firstly performing a heat treatment at 420° C.-520° C., and then heating to 650° C.-750° C. for a secondary heat treatment to obtain rare earth oxide modified bamboo charcoal powder; The preparation method of the zinc oxide modified tourmaline powder comprises the following steps: Step a, dissolving zinc salt in an alcohol solution, adding a strong base, mixing evenly, separating the solid from the liquid, washing, and drying to obtain zinc oxide powder; Step b, adding tourmaline powder to the zinc oxide powder for ball milling, heating to 200° C.-300° C. for calcination to obtain zinc oxide modified tourmaline powder.

2. The mortar material capable of releasing negative ions according to claim 1, characterized in that: In S1, the temperature is increased by programmed temperature increase, and the rate of temperature increase is 10°C / min-15°C / min; and / or In S1, the pretreatment heat preservation time is 3h-6h; and / or In S1, the rotation speed of the ball mill is 800 rpm-1000 rpm, and the ball milling time is 30 min-40 min.

3. The mortar material capable of releasing negative ions according to claim 1, characterized in that: In S2, the mass ratio of the pretreated bamboo charcoal powder to the rare earth oxide is 10:1-10:1.5; and / or In S2, the holding time of the primary heat treatment is 2h-4h; and / or In S2, the holding time of the secondary heat treatment is 5h-8h; and / or In S2, the primary heat treatment and the secondary heat treatment are both heated by programmed temperature increase, wherein the heating rate of the primary heat treatment is 10°C / min-20°C / min, and the heating rate of the secondary heat treatment is 5°C / min-10°C / min.

4. The mortar material capable of releasing negative ions according to claim 1, characterized in that: In step a, the zinc salt is any one of zinc acetate, zinc chloride, zinc sulfate or zinc nitrate; and / or In step a, the strong base is potassium hydroxide or sodium hydroxide; and / or In step a, the alcohol solution is a 50%-65% ethanol solution; and / or In step a, the mass volume ratio of the zinc salt to the alcohol solution is 1g:3mL-1g:5mL; and / or In step a, the mass ratio of the zinc salt to the strong base is 1:0.05-3:0.

1.

5. The mortar material capable of releasing negative ions according to claim 1, characterized in that: In step b, the mass ratio of the zinc oxide powder to the tourmaline powder is 1:8-1:10; and / or In step b, the ball milling speed is 500 rpm-800 rpm, and the ball milling time is 20 min-40 min; and / or In step b, the calcination time is 3h-6h; and / or In step b, the temperature is increased by programmed temperature increase at a rate of 5°C / min-10°C / min.

6. The method for preparing the mortar material capable of releasing negative ions according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: weighing various raw material components according to the designed proportion, and evenly mixing the weighed components to obtain a mortar material capable of releasing negative ions.

7. Use of the mortar material capable of releasing negative ions as described in any one of claims 1 to 5 or the mortar material capable of releasing negative ions prepared by the method for preparing the mortar material capable of releasing negative ions as described in claim 6 in the field of building materials.

Citation Information

Patent Citations

  • Inner wall decoration mortar and construction method thereof

    CN101857408A

  • Preparation of rare earth and white bamboo charcoal composite micro-powder

    CN102114262A

  • Negative ion mortar for building walls and preparation method of negative ion mortar

    CN107555893A

  • Negative oxygen ion air purifying agent, preparation method and application thereof

    CN112246083A